Stimuli-responsive nanocarriers for targeted drug delivery / Muhammad Raza Shah, Tooba Jabri, Maria Khalid. - Shah, Muhammad Raza (Professor of chemistry); Jabri, Tooba; Khalid, Maria (Woodhead Publishing series in biomaterials., 2024)
'Stimuli-Responsive Nanocarriers for Targeted Drug Delivery' presents a comprehensive overview of the most significant physical and chemical stimuli-responsive drug delivery systems. The book reviews targeted and controlled drug delivery systems and how nanocarriers can be used to improve the pharmacokinetics of drugs in biological systems, such as increasing utilization rate and reducing toxicity and side effects. After a key introduction to the topic, a range of nanocarrier types is assessed before exploring the clinical translation challenges and considerations involved.